2021
DOI: 10.3390/nano11040987
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivation Treatment with Mixed Acid and Heat on Titanium Implants Fabricated by Selective Laser Melting Enhances Preosteoblast Cell Differentiation

Abstract: Selective laser melting (SLM) is a promising technology capable of producing individual characteristics with a high degree of surface roughness for implants. These surfaces can be modified so as to increase their osseointegration, bone generation and biocompatibility, features which are critical to their clinical success. In this study, we evaluated the effects on preosteoblast proliferation and differentiation of titanium metal (Ti) with a high degree of roughness (Ra = 5.4266 ± 1.282 µm) prepared by SLM (SLM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…Furthermore, the relative gene expression of ALP and COL were up-regulated for TICT samples associated with calcium titanate produced after 48 h in SBF [65]. Similar results were found for MC3T3-E1 cells seeded on a selective laser melting -Ti surface, which showed a strong tendency towards osteogenic differentiation by significantly increased expression of alkaline phosphatase, osteocalcin, Runx2 and osteopontin [66].…”
Section: Discussionsupporting
confidence: 74%
“…Furthermore, the relative gene expression of ALP and COL were up-regulated for TICT samples associated with calcium titanate produced after 48 h in SBF [65]. Similar results were found for MC3T3-E1 cells seeded on a selective laser melting -Ti surface, which showed a strong tendency towards osteogenic differentiation by significantly increased expression of alkaline phosphatase, osteocalcin, Runx2 and osteopontin [66].…”
Section: Discussionsupporting
confidence: 74%
“…These micro/nanoscale structures observed through SEM on the AHT-Sr implant surface may enhance bone formation. In addition, osteoblast attachment could be promoted by implants with higher surface hydrophilicity ( Le et al, 2021 ). Kubo et al (2009) have reported that uniformly distributed 300-nm nano surface structures significantly enhance ALP activity, mRNA expression of Col1, and Ocn, and total calcium deposition in BMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…The spheroidal‐like bone apatite was only generated on the surface of SLM Ti using acid‐heat treatment. [ 145 ] In addition, the microhardness of SLM implants was increased by acid‐heat treatment due to the formation of oxide coating. [ 146 ] Table 1 summarizes the acid treatment studies of SLM Ti and its alloys.…”
Section: Chemical Methodsmentioning
confidence: 99%
“…Surface morphologies of four Ti samples soaked in SBF for 1 day. Reproduced with permission [145]. Copyright 2021, MDPI.…”
mentioning
confidence: 99%